2023
DOI: 10.1177/21676968231182755
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Efficacy in Initiating Romantic Relationships and Single Emerging Adults’ Well-Being

Abstract: Using data from 313 single emerging adults living in the United States, we explored initiation-efficacy (i.e., perceived abilities related to initiating romantic relationships) and if it was associated with well-being (life satisfaction, happiness with romantic experiences, and loneliness). Most participants indicated that it is not easy to ask someone out or tell someone they are interested in them and talking with someone they have feelings for is awkward. Initiation-efficacy was associated with well-being. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Our work has consistently found that for single young adults, relationship (dis)interest is associated with well‐being, including their satisfaction with their romantic experiences. Generally, we have found that for single young adults, scoring higher in relationship dismissal is associated with greater life satisfaction and love life satisfaction, but scoring higher in relationship desire is associated with greater loneliness (Watkins et al, under review; Watkins & Beckmeyer, 2020; Watkins & Beckmeyer, under review). We interpret these findings as indicating that being less interested in relationships allows young adults to frame their singlehood more positively, likely as a personal choice and within their own control.…”
Section: Empirical Insights About Singlehoodmentioning
confidence: 97%
“…Our work has consistently found that for single young adults, relationship (dis)interest is associated with well‐being, including their satisfaction with their romantic experiences. Generally, we have found that for single young adults, scoring higher in relationship dismissal is associated with greater life satisfaction and love life satisfaction, but scoring higher in relationship desire is associated with greater loneliness (Watkins et al, under review; Watkins & Beckmeyer, 2020; Watkins & Beckmeyer, under review). We interpret these findings as indicating that being less interested in relationships allows young adults to frame their singlehood more positively, likely as a personal choice and within their own control.…”
Section: Empirical Insights About Singlehoodmentioning
confidence: 97%
“…Because romantic involvement appears to be a salient developmental task that may promote young adult well-being, being single during young adulthood has often been framed as costly for growth and development during this stage of the life course (e.g., Ta et al, 2017). However, some scholars have begun challenging the deficitperspective of singlehood (DePaulo, 2014(DePaulo, , 2023Pepping et al, 2018) by exploring how young adults' romantic beliefs and desires, personality characteristics, and life circumstances shape their experiences of being single and its connections with well-being (Beckmeyer & Cromwell, 2019;Beckmeyer & Jamison, 2023a;Girme et al, 2016;Lehmann et al, 2015;Sharp & Ganong, 2011;Watkins & Beckmeyer, 2023).…”
Section: Abstract Emerging Adulthood Romantic Development Singlehood ...mentioning
confidence: 99%